Effect of Moringa (Moringa oleifera) Leaf Flour Supplementation on Total Antioxidant Content of Sprague Dawley Rat Serum Given High-Fat Diet - Sherlin Regina Jami; Siti Fatimah-Muis; Ahmad Syauqy; Kusmiyati Tjahjono; Gemala Anjani (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2022)
Background: Moringa oleifera leaf is high in quercetin which can be a source of exogenous antioxidants. Together with endogenous antioxidants, both the antioxidants will be able to counteract oxidative stress conditions.Objectives: To analyze the effect of Moringa leaves flour supplementation on Total Antioxidants Content (TAC) of Sprague Dawley (SD) rat serum given a high-fat diet (HFD). Materials and Methods: A randomized control group post-test design was used on 24 SD rats which were divided into 4 groups, namely healthy control (K1), HFD (K2), supplementation with Moringa leaf flour at a dose of 100 mg/100 g BW/day (K3), and a dose of 200 mg/100 g BW/day (K4). After 28 days of supplementation, serum TAC was analyzed using the ELISA method. Data analysis used Paired-T Test, One Way ANOVA, and Post-Hoc Bonferroni follow-up test.Results: The results showed that the TAC of groups K1, K2, K3, and K4 respectively were 4.806 ± 0.239, 1.323 ± 0.292, 4.020 ± 0.239, and 5.123 ± 0.695. There was a significant difference in serum TAC (p=0.000) between supplementation groups. Significant differences in serum TAC were also found in the supplementation group compared to the HFD control group.Conclusion: Moringa leaves flour supplementation for 28 days at a dose of 200 mg/100 g BW/day increases serum total antioxidant content higher than at a dose of 100 mg/100 g BW/day.